Effective Exciton Dissociation and Reduced Charge Recombination in Thick‐Film Organic Solar Cells via Incorporation of Insulating Polypropylene. Issue 8 (12th August 2019) - Wang, Tong; Yang, Xiao-Yu; Bi, Peng-Qing; Niu, Meng-Si; Feng, Lin; Liu, Jian-Qiang; Hao, Xiao-Tao
Abstract : In article no. 1900087, Jian‐Qiang Liu, Xiao‐Tao Hao, and co‐workers introduce polypropylene into a bulk heterojunction consisting of donors and acceptors to fabricate effective organic solar cells with a thick active layer. The incorporation of polypropylene improves the crystallinity of the donor and reduces the aggregation size of the acceptor, which facilitates exciton dissociation and charge transition and inhibits the recombination of carriers.